Keefektifan Teknik Konseling Kelompok Untuk Mengurangi Kecemasan Siswa Berbicara Di Depan Kelas - Yuspa Kurnia; Handayani Sura’; Ismail Ismail (EduPsyCouns: Journal of Education, Psychology and Counseling, 2022)
Abstract: This study aims to reduce the level of students when speaking in front of the class or in public, in this study using quantitative methods with the type of experimental research. The results of the test antiety of students speaking in front of the eleventh grade can decrease after being given or participating in group counseling activities. Based on the score of the questionnaire before the pretest, the average value was 111,08 and after the post-test, the students’ speaking anxiety decreased with the questionnaire score obtained an average value of 82,81. Thus it can be concluded that the application of group counseling can reduce the level of anxiety of students speaking in front of the class. This means that the more treatment is given in the form of group counseling, it is followed by a reduced level of anxiety in students speaking in front of the class. Abstrak: Penelitian ini bertujuan untuk mengurangi tingkat kecemasan siswa saat berbicara di depan kelas maupun di depan umum. Dalam penelitian tersebut menggunakan metode kuantitatif dengan jenis penelitian eksperimen. Hasil uji coba kecemasan siswa berbicara di depan kelas XI dapat menurun setelah diberikan atau mengikuti kegiatan konseling kelompok. Berdasarkan skor angket sebelum pretest diperoleh nilai rata-rata sebesar 111,08 dan setelah postest kecemasan berbicara siswa mengalami penurunan dengan skor angket diperoleh nilai rata-rata 82,81. Dengan demikian dapat di simpulkan bahwa penerapan konseling kelompok dapat mengurangi tingkat kecemasan siswa berbicara di depan kelas. Artinya semakin di berikan perlakuan berupa konseling kelompok, maka di ikuti dengan berkurangnya tingkat kecemasan siswa berbicara di depan kelas.